Pembinaan Akhlak Santri Dalam Membangun Pendidikan Karakter Religius Melalui Peraktek Dakwah Di Pesantren Nurul Bantany Kota Serang - Dedi Wahyudi; Zakariyah Zakariyah; Ashari Ashari (CV. ITTC INDONESIA, 2025)
This study aims to describe and analyze (1) the moral development of Islamic boarding school students, (2) the role of Islamic da'wah character in the lives of Islamic boarding school students, and (3) the process of building character education. This study uses a qualitative approach with a case study approach. The results of the study indicate that moral development in Islamic boarding schools is carried out through the example of the caretakers and ustaz, the habituation of daily worship, scheduled religious activities, and the strengthening of moral values through social interaction and intensive supervision. The role of Islamic da'wah character is evident in the behavior of Islamic boarding school students who actively preach through oral, written, and exemplary attitudes, both in the internal and external environments of the Islamic boarding school. The character education process is built through an integrated curriculum, the instillation of spiritual and social values, and the strengthening of discipline and responsibility in daily life. This study provides theoretical implications in the development of an Islamic boarding school-based character development model, as well as practical implications for Islamic educational institutions in designing holistic strategies for developing Islamic boarding school character development. This study has limitations in the scope of a single location and does not include the perspective of alumni in assessing the long-term success of Islamic boarding school character programs.